Education and Facilitation Methods for Extension - Kathryn A. Stofer (EDIS)
This document outlines, compares, and contrasts methods that Extension professionals can use with their stakeholders to achieve these goals, including ways to turn traditional one-strategy program formats into programs incorporating multiple facilitation strategies.